PERKEMBANGAN ISLAM DI INDONESIA MASA KEMERDEKAAN (SUATU KAJIAN HISTORIS) - Abd. Rasyid Rahman (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2017)
The process of Islamization in Indonesia was peaceful, conducted by Islamic preachers who happened to be traders. Those trading activities were supporting elements in the Islamization process. The development of Islam in Indonesia in the independence era especially in the Old Order era (under the Constitution of 1945, of Republic of the United States of Indonesia, and of the Provisional Constitution of 1950) was in the stage of actualization of religious teachings as the foundation in state-building. In the New Order era the development of Islam was marked by therenewal of the teaching of Islam. In the Reformasi period, teh development of Islam was marked by the growing calls for the implementation of Islamic law.